1985
DOI: 10.1159/000249378
|View full text |Cite
|
Sign up to set email alerts
|

Acrokeratoelastoidosis: A Spectrum of Diseases

Abstract: Two familial cases of acrokeratoelastoidosis (AKE) are reported. As a quite uncommon feature, both showed a distinct violaceous hue in addition to the characteristic clinicopathological changes. Furthermore a case of keratoelastoidosis marginalis of the hands, also showing involvement of the feet, is described. This latter syndrome may cause confusion with AKE, but appears to be a separate entity. The classification of AKE is discussed. It is suggested that AKE is a syndrome with a broad spectrum of clinical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
28
0
3

Year Published

1995
1995
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 7 publications
3
28
0
3
Order By: Relevance
“…146 In addition to presumptively acquired cases, both sporadic and autosomal dominant forms of AKE have been reported. 146,148,[151][152][153][154][155] There is some evidence to suggest that the pathogenesis of AKE may be due to a failure of elastic fiber synthesis rather than degeneration. Results of an ultrastructural study showed that fibroblasts of lesional skin contain dense granules at the periphery of their cytoplasm, while extracellular elastic fibers are deficient; such findings are consistent with a defect in the secretion of elastic material.…”
Section: Acrokeratoelastoidosismentioning
confidence: 99%
“…146 In addition to presumptively acquired cases, both sporadic and autosomal dominant forms of AKE have been reported. 146,148,[151][152][153][154][155] There is some evidence to suggest that the pathogenesis of AKE may be due to a failure of elastic fiber synthesis rather than degeneration. Results of an ultrastructural study showed that fibroblasts of lesional skin contain dense granules at the periphery of their cytoplasm, while extracellular elastic fibers are deficient; such findings are consistent with a defect in the secretion of elastic material.…”
Section: Acrokeratoelastoidosismentioning
confidence: 99%
“…hen wurden [1,8], können sie doch, wegen fehlender Elastorrhexis, eher als Varianten oder Phasen der hereditären fokalen akralen Hyperkeratose angesehen werden [31]. Möglicherweise handelt es sich sogar um eine einzige Entität.…”
unclassified
“…Weitere Differentialdiagnosen der fokalen akralen Hyperkeratose sind die Keratoelastoidosis marginalis der Hände [1,20] [12].…”
unclassified
“…The papules in acrokeratoelastoidosis are characteristically small, shiny, firm, and yellowish, and grouped over the dorsal hand and lateral margins of the palms and soles, the space between the thumb and forefinger, on the anterior surface of the lower legs, and over the knuckles and nail folds 2,3 . Lesions with a distinct violaceous hue have also been reported 4 . The papules are usually asymptomatic.…”
Section: Discussionmentioning
confidence: 99%